Study of the Lithium Retention by Salts Crystallised from Natural Brines - M'nif, A.; Hamzaoui, H.A.; Rokbani, R. (Asian Journal of Chemistry, 2010)
Natural brines may be a source of lithium. However the extraction of this element can be affected by solar evaporation. Indeed we put in evidence the existence of retention phenomenon of this element by the crystallized salts. Regarding this phenomenon, we determined the retention mode (coating solution, adsorption, and substitution) and establish relations between retention ratios and lithium concentrations in the solutions.